If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -8 = 7x + 7 + -6x Combine like terms: -2 + -8 = -10 -10 = 7x + 7 + -6x Reorder the terms: -10 = 7 + 7x + -6x Combine like terms: 7x + -6x = 1x -10 = 7 + 1x Solving -10 = 7 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -10 + -1x = 7 + 1x + -1x Combine like terms: 1x + -1x = 0 -10 + -1x = 7 + 0 -10 + -1x = 7 Add '10' to each side of the equation. -10 + 10 + -1x = 7 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = 7 + 10 -1x = 7 + 10 Combine like terms: 7 + 10 = 17 -1x = 17 Divide each side by '-1'. x = -17 Simplifying x = -17
| 441-7x=81(x+2) | | 12-aw=cw | | 21/7-31/14 | | (5+3x)4-2x=0 | | 36y=7(5y-2) | | 3-x=4x-8 | | Y-2/3=8/3 | | 31=6+9(k+7) | | 2-7R=-75 | | 65-92= | | -12=12y | | 4/x+6=8/3x+5 | | 6x^2+7x-25=0 | | -(1-6b)=-3+2(2b-4) | | 3h-7=-2 | | 90=(3x-5)+(2x) | | 6x^2+7x-21=0 | | y=-5/7x-4 | | 123+180=180 | | -2ab-ab= | | (-92)+63= | | 5g+9=5 | | 5(c-2)=5b-3 | | 6-4=7X-9X-8 | | 5g+9=-5 | | -2r=-34 | | 1.2(x-5)=1.6(2x+5) | | (x+3)(x+3)=12*x | | (2m+3)(6m-2)= | | 10x+-9x= | | 3r^2-9r-17=2r^2-5-8r | | 44x+7=73 |